STRATEGI BERTAHAN USAHA MIKRO DI WILAYAH PARIWISATA KOTA PADANG DI TENGAH PANDEMI COVID-19 - Muthia Ulfah; Bayu Kurnia (Universitas Islam Negeri Imam Bonjol Padang, 2021)
This study aimed to analyze the impact of the Covid-19 pandemic on micro enterprises around Padang City tourism area, especially on their income and survival strategies. To achieve these objectives, this study used qualitative research methods. The results showed that the Covid-19 Pandemic influenced the income of micro enterprises araound Padang City tourism area. The level of impact varied depending on the type of business and their survival strategy. The strategies carried out by micro enterprises were: 1) Active strategies, by improving product quality, increasing business variety, doing digital marketing, and improving service quality; 2) Passive strategies, by utilizing savings and increasing production efficiency; 3) Network strategy, by accessing grants, loans, or financing from financial institutions. The better strategy to reduce the impact of Covid-19 pandemic was implementing strategies that can provide value added and ensure business sustainability.